2018
DOI: 10.1186/s12933-018-0716-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linagliptin on endothelial function and postprandial lipids in coronary artery disease patients with early diabetes: a randomized, placebo-controlled, double-blind trial

Abstract: BackgroundEarly glucose lowering intervention in subjects with type 2 diabetes mellitus was demonstrated to be beneficial in terms of micro- and macrovascular risk reduction. However, most of currently ongoing cardiovascular outcome trials are performed in subjects with manifest atherosclerosis and long-standing diabetes. Therefore, the aim of this study is to investigate the effects of the dipeptidylpeptidase-4 inhibitor linagliptin in subjects with coronary artery disease (CAD) but early type 2 diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Both at fasting and post-prandially we studied endothelial function by two different methods, at microvascular level using Ach-induced vasodilatation and at small artery level by measuring reactive hyperhemia, and we measured VCAM-1 and E-selectin as endothelial markers. Endothelial function was shown to impair after glucose or fat load in relation with oxidative stress both in healthy individuals and in patients with type 2 diabetes (49). Such changes did not occur in our patients as we previously reported in patients with type 2 diabetes (22).…”
Section: Discussionsupporting
confidence: 79%
“…Both at fasting and post-prandially we studied endothelial function by two different methods, at microvascular level using Ach-induced vasodilatation and at small artery level by measuring reactive hyperhemia, and we measured VCAM-1 and E-selectin as endothelial markers. Endothelial function was shown to impair after glucose or fat load in relation with oxidative stress both in healthy individuals and in patients with type 2 diabetes (49). Such changes did not occur in our patients as we previously reported in patients with type 2 diabetes (22).…”
Section: Discussionsupporting
confidence: 79%
“…Given observed counteracting effects against stroke‐mimic high‐glucose and hypoxic conditions by DPP‐4 inhibitor, for example, increased expression of NOS and VEGF, as well as the essential role of NOS and VEGF in cerebrovascular endothelial health, it could be suggested that DPP‐4 inhibitor may have impact on the vascular endothelial function. Interestingly, previous studies have reported controversial results about the effects of DPP‐4 inhibitor on endothelial function . On this basis, further investigations are in demand which constitute our future work.…”
Section: Discussionmentioning
confidence: 95%
“…The CVD group consisted of five studies ( 31 , 32 , 37 , 42 , 45 ) in which participants were all diagnosed with CVD (hypertension, coronary atherosclerosis, or carotid atherosclerotic disease). The non-CVD group consisted of 25 studies ( 27 30 , 33 36 , 38 41 , 43 , 44 , 46 49 ), none of whom were diagnosed with CVD. The participant characteristics and interventions in the studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%